Optimization of carrageenan extraction from Kappaphycus alvarezii seaweed using a factorial design study - Azren Aida, Asmawi; Muhammad Alif Farhan, Mohd Yusof; Muhammad Amirul Husni, Abdul Hadi; Khadijah Husna, Abd Hamid; Badhrulhisham, Abdul Aziz; Nurul Aini, Mohd Azman (Penerbit Universiti Teknologi Malaysia, 2026)
Carrageenan is a sulfated polysaccharide extracted from seaweeds and is pivotal in various industries due to its gelling, thickening, and stabilizing properties. Despite its widespread use, the efficiency of carrageenan extraction significantly influences its quality and market value. This study aims to optimize the extraction process of semi-refined carrageenan from Kappaphycus alvarezii seaweed using a factorial design method, focusing on maximizing yield and film characteristics while maintaining process sustainability and cost-effectiveness. Two process parameters with optimal mechanical properties (OPT 1) and yield (OPT 2) were selected based on the predictive model generated by the factorial design analysis. The results showed that soaking time positively influences gel strength, whereas prolonged extraction time reduces gel strength. Higher extraction temperatures increase gel viscosity, whereas increased KOHCarrageenan is a sulfated polysaccharide extracted from seaweeds and is pivotal in various industries due to its gelling, thickening, and stabilizing properties. Despite its widespread use, the efficiency of carrageenan extraction significantly influences its quality and market value. This study aims to optimize the extraction process of semi-refined carrageenan from Kappaphycus alvarezii seaweed using a factorial design method, focusing on maximizing yield and film characteristics while maintaining process sustainability and cost-effectiveness. Two process parameters with optimal mechanical properties (OPT 1) and yield (OPT 2) were selected based on the predictive model generated by the factorial design analysis. The results showed that soaking time positively influences gel strength, whereas prolonged extraction time reduces gel strength. Higher extraction temperatures increase gel viscosity, whereas increased KOH concentration and extraction times lower viscosity due to structural breakdown. Besides, OPT 1 and OPT 2 film analyses show tensile strengths of 34.40 MPa and 34.52 MPa, respectively, with superior flexibility, and elongation at a break (EAB) of 31.30% outperforming commercial films (19.18%). These results highlight the films' balance of durability and adaptability, positioning them as viable and sustainable packaging alternatives. concentration and extraction times lower viscosity due to structural breakdown. Besides, OPT 1 and OPT 2 film analyses show tensile strengths of 34.40 MPa and 34.52 MPa, respectively, with superior flexibility, and elongation at a break (EAB) of 31.30% outperforming commercial films (19.18%). These results highlight the films' balance of durability and adaptability, positioning them as viable and sustainable packaging alternatives.